Resident-Memory T Cells in Tissue-Restricted Immune Responses: For Better or Worse? - Steinbach, Karin; Vincenti, Ilena; Merkler, Doron (Frontiers in Immunology, 2018)
Tissue-resident-memory CD8+ T cells (TRM) have been described as a non-circulating memory T cell subset that persists at sites of previous infection. While TRM in all non-lymphoid organs probably share a core signature differentiation pathway, certain aspects of their maintenance and effector functions may vary. It is well-established that TRM provide long-lived protective immunity through immediate effector function and accelerated recruitment of circulating immune cells. Besides immune defense against pathogens, other immunological roles of TRM are less well-studied. Likewise, evidence of a putative detrimental role of TRM for inflammatory diseases is only beginning to emerge. In this review, we discuss the protective and harmful role of TRM in organ-specific immunity and immunopathology as well as prospective implications for immunomodulatory therapy.